Novel heterotopic continental ileal reservoir based on the Mitrofanoff principle: a case report and review of the literature - Yakun, Hou; Guofan, Dong; Qiang, Liu; Azat, Bahtiyar; Rexiati, Mulati; Yujie, Wang; Wenguang, Wang (Frontiers in Surgery, 2023)
For patients undergoing radical cystectomy with standard lymphadenectomy for bladder cancer, appropriate urinary diversion (with a pouch and conduit) improves postoperative quality of life, reduces postoperative complications, and prolongs survival. We developed a novel heterotopic ileal reservoir to achieve these goals. This report describes the methodology involved and the incidence of intraoperative and postoperative complications. Three patients who underwent novel heterotopic ileal reservoir creation following radical cystectomy and standard lymphadenectomy (for bladder cancer) were evaluated. The ileum served as a pouch in which 2 the ureters and appendix were implanted by extramural tunnelling. The appendix served as a conduit and pelvic reperitonealization was performed. Operative times, intraoperative blood loss, time to intestinal function recovery, incidence of intestinal obstruction and ureteric reflux, and bladder volumes and continence levels were evaluated. The surgical intervention was successful with operation times ranging 410-525 minutes, blood loss ranging 300-700 mL, and recovery time for intestinal function ranging 3-5 days. The postoperative hospitalization time was 11-15 days. Subileus occurred in patient B, who recovered after fasting and fluid replacement. Patients B and C achieved complete continence 6 weeks after surgery, while patient A experienced umbilical urine leakage with catheterization time intervals that exceeded 4 hours. At 3 months after surgery, the bladder capacities of all patients ranged 250-370 mL. Follow-up cystography suggested the presence of bilateral ureteral reflux in patient A, with mild and moderate reflux on the left right sides, respectively. All patients achieved complete continence. Patients were followed for 3-9 months postoperatively; chest and abdominal computed tomography and cystography showed absence of hydronephrosis, recurrence, or distant metastasis during this period. The novel heterotopic continent ileal reservoir described in this study may be suitable for selected patients. The surgical procedure is safe when performed by well-trained and highly experienced urologists.